Optimal First-Line Treatment for Helicobacter pylori Infection: Recent Strategies - Ju Yup Lee; Kyung Sik Park (Gastroenterology Research and Practice)
A new treatment strategy is needed, as the efficacy of triple therapy containing clarithromycin—the current standard treatment for Helicobacter pylori infection—is declining. Increasing antibiotic resistance of H. pylori is the most significant factor contributing to eradication failure. Thus, selecting the most appropriate regimen depending on resistance is optimal, but identifying resistance to specific antibiotics is clinically challenging. In a region suspected to have high clarithromycin resistance, bismuth quadruple therapy and so-called nonbismuth quadruple therapies (sequential, concomitant, and sequential-concomitant hybrid) are some first-line regimen options. However, more research is needed regarding appropriate second-line treatments after first-line treatment failure. Tailored therapy, which is based on antibiotic sensitivity testing, would be optimal but has several limitations for clinical use, and an alternative technique is required. A novel potassium-competitive acid blocker-based eradication regimen could be a valuable eradication option in the near future.